Case Report: Mineralized Pulmonary Artery Thrombi in Two Dogs Treated for Meningoencephalitis of Unknown Origin - Rosen, Suzanne; Benedicenti, Leontine; Petesch, Scott; Reetz, Jennifer; Galban, Evelyn Marie (Frontiers in Veterinary Science, 2020)
Meningoencephalitis of unknown etiology (MUE) is a relatively common and very serious canine neurologic condition, which is typically associated with a poor long term prognosis despite treatment. This case series chronicles two dogs diagnosed with suspected MUE who were treated with long term corticosteroids and cytosine arabinoside and lived well beyond the typical survival time for this condition. Both eventually succumbed to respiratory signs associated with mineralized thrombi in their pulmonary arteries. Adverse effects from the two drugs used for treatment are reviewed in order to propose a possible mechanism to explain how long term use of these medications could result in such a phenomenon.